2018
DOI: 10.1002/jts.22279
|View full text |Cite|
|
Sign up to set email alerts
|

Secondary Traumatic Stress and Burnout Among Refugee Resettlement Workers: The Role of Coping and Emotional Intelligence

Abstract: To promote a better understanding of the impact of refugee resettlement work on refugee resettlement workers, this study examined the prevalence rates of deleterious mental health and occupational outcomes, such as secondary traumatic stress and burnout, among a sample of 210 refugee resettlement workers at six refugee resettlement agencies in the United States. The study also explored coping mechanisms used by service providers to manage work-related stress and the influence of such strategies and emotional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 57 publications
(67 reference statements)
7
44
3
2
Order By: Relevance
“…This was coupled with additional work demands that contributed to the overall increased work‐related stress experienced by providers. These findings align with literature on Secondary Trauma Stress, which highlight that health and social service providers, especially those supporting marginalised clients, often experience emotional and psychological distress, as well as physical burnout in the workplace (Akinsulure‐Smith, Espinosa, Chu, & Hallock, 2018; Beck, 2011; Cieslak et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…This was coupled with additional work demands that contributed to the overall increased work‐related stress experienced by providers. These findings align with literature on Secondary Trauma Stress, which highlight that health and social service providers, especially those supporting marginalised clients, often experience emotional and psychological distress, as well as physical burnout in the workplace (Akinsulure‐Smith, Espinosa, Chu, & Hallock, 2018; Beck, 2011; Cieslak et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Park, Aldwin, Fenster, and Snyder (2008) found that adaptive coping strategies such as seeking support were linked to less secondary traumatic stress. However, whereas Akinsulure- Smith, Espinosa, Chu, and Hallock (2018) found positive correlations between avoidance as well as distraction strategies and secondary traumatic stress, McCann and Lubman (2018) found that more avoidance and distraction was associated with less secondary traumatic stress. In fact, trauma scholars suggest that avoidance and distraction may give the individual experiencing trauma the space and time needed to reevaluate the traumatic event and find a positive meaning (Linley & Joseph, 2005).…”
Section: The Role Of Coping and Predisaster Stressors On Secondary Stmentioning
confidence: 90%
“…Results also provide important information about the role of coping when dealing with secondary exposure and secondary traumatic stress. Although the trauma literature continues to categorize coping as adaptive or maladaptive (Akinsulure- Smith et al, 2018;McCann & Lubman, 2018), these classifications may not be adequate. Participants in our study used avoidance, distraction, and minimization to cope with the destruction caused by Hurricane María.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Hence, practitioners working with refugees who unequivocally meet DSM-5 Criteria A, are exposed to risks for secondary traumatic stress and should be considered a priority when exploring this phenomenon [ 50 , 51 ]. Surprisingly, this matter only started getting more attention recently, and only a few studies have explored secondary traumatization among service providers working with refugees [ 50 52 ].…”
Section: Introductionmentioning
confidence: 99%